2020
DOI: 10.1016/j.psychsport.2020.101757
|View full text |Cite
|
Sign up to set email alerts
|

Does learning a skill with the expectation of teaching it impair the skill’s execution under psychological pressure if the skill is learned with analogy instructions?

Abstract: Objective Having learners practice a motor skill with the expectation of teaching it (versus an expectation of being tested on it) has been revealed to enhance skill learning. However, this improvement in skill performance is lost when the skill must be performed under psychological pressure due to ‘choking under pressure.’ The present study will investigate whether this choking effect is caused by an accrual of declarative knowledge during skill practice and could be prevented if a technique (ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…Similarly, learning by analogy (as compared to traditional 'explicit' instruction) has been shown to be effective for maintaining performance under pressure (Cabral et al, 2020;Lam et al, 2009b;Liao & Masters, 2001;Lola et al, 2021;Zeniya & Tanaka, 2021), under time constraints , when fatigued (Poolton et al, 2007a), and in individuals whose working memory capacity is otherwise compromised (Capio et al, 2020;Koedijker et al, 2007Koedijker et al, , 2011Lee et al, 2019;Tse, Fong et al, 2017;; for a meta-analysis see Cabral et al, 2022). By drawing on simple rules, motor heuristics and movement analogies help to effectively manage cognitive resources, allowing stable movement selection and movement execution in demanding circumstances.…”
Section: Simplified Information Processing In Actionmentioning
confidence: 99%
“…Similarly, learning by analogy (as compared to traditional 'explicit' instruction) has been shown to be effective for maintaining performance under pressure (Cabral et al, 2020;Lam et al, 2009b;Liao & Masters, 2001;Lola et al, 2021;Zeniya & Tanaka, 2021), under time constraints , when fatigued (Poolton et al, 2007a), and in individuals whose working memory capacity is otherwise compromised (Capio et al, 2020;Koedijker et al, 2007Koedijker et al, , 2011Lee et al, 2019;Tse, Fong et al, 2017;; for a meta-analysis see Cabral et al, 2022). By drawing on simple rules, motor heuristics and movement analogies help to effectively manage cognitive resources, allowing stable movement selection and movement execution in demanding circumstances.…”
Section: Simplified Information Processing In Actionmentioning
confidence: 99%
“…Bu düzenekte beceri puanı topun merkeze yakınlığı ile belirlenmekte, hedefi tutturma başarısının atış sayısı arttıkça artması motor öğrenmenin bir göstergesi olarak ifade edilmektedir [16]. Mini golf düzeneklerindeki beceri puanı hesaplanırken, atışların hedef noktaya ne kadar yakın olduğunu belirten Radial Error (RE) değeri ve atışların birbiriyle ne kadar tutarlı olduğunu gösterene Bivariat Variable Error (BVE) değerleri kullanılmaktadır [17]. Bu formüllerin kullanılması gerektiği ilk olarak Hancock ve ark.…”
Section: Motor öğRenme Sürecini Nasıl Değerlendirebiliriz?unclassified
“…In most of these studies, putting performance has been measured as the distance from the stop position of the ball to a target or hole. For that purpose, two main methods have been used: radial error 13 or a dartboard score around the target 11 . However, published studies have not coincided with the number of shots completed in the experimental protocols.…”
Section: Introductionmentioning
confidence: 99%
“…However, published studies have not coincided with the number of shots completed in the experimental protocols. Thus, studies in which 5 to 10 trials were performed 11 13 until studies that used protocols of 40 to 50 trials were found 7 , 14 .…”
Section: Introductionmentioning
confidence: 99%